Primary Leptomeningeal Melanoma of the Cervical Spine Mimicking a Meningioma—A Case Report - Marx, Sascha; Fleck, Steffen K.; Manwaring, Jotham; Vogelgesang, Silke; Langner, Soenke; Schroeder, Henry W.S. (Journal of Neurological Surgery Reports, 2014)
Background and Importance Primary leptomeningeal melanoma (PLM) is highly malignant and exceedingly rare. Due to its rarity, diagnostic and treatment paradigms have been slow to evolve. We report the first case of a PLM that mimics a cervical spine meningioma and then discuss the current clinical, radiologic, and pathologic diagnostic methodologies as well as expected outcomes related to this disease.Clinical Presentation A 54-year-old woman presented a dural-based extramedullary solid mass ventral to the C2–C3 spinal cord causing spinal cord compression without cord signal changes, characteristic of meningioma. Intraoperative microscopic inspection revealed numerous black spots littering the surface of the dura; the tumor itself was yellow in appearance and had a soft consistency. Pathologic analysis of the specimen revealed a malignant melanin-containing tumor. No primary site was found, so a diagnosis of primary leptomeningeal melanoma was made, and the patient subsequently received interferon therapy. To date (2 years postoperatively), no local or systemic recurrence of the tumor has been identified.Conclusion As with most rare tumors, case reports constitute the vast majority of references to PLM. Only an increased awareness and an extensive report of each individual case can help diagnose and clarify the nature of PLM. Clinicians need to be aware of such malignant conditions when diagnosing benign tumoral lesions of the spine such as meningiomas.
Keywords: CSF analysis; histology; meningioma; misdiagnosis; MRI characteristics; primary leptomeningeal melanoma